2021
DOI: 10.3390/ijerph18189565
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Parental Involvement and Mathematics Achievement of Chinese Early Adolescents: Multiple Mediating Roles of Mental Health and Mathematics Self-Efficacy

Abstract: This study conceptualized the multidimensional construct of parental involvement, including cognitive involvement, behavioral involvement, and personal involvement, and examined the mediating effects of student’s mental health and mathematics self-efficacy. Questionnaires were administered to 2866 early adolescents and their parents in China; structural equation modeling and bias-corrected bootstrap methods were used. The results show that different dimensions of parental involvement had different effects on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…The role of parental involvement that has a positive and significant effect on student performance is in line with some previous relevant research [21,22]. Purnomo and colleagues [2] stated that learning from home forces parents to be involved in their children's learning, especially their supervision of their children's work.…”
Section: Discussionsupporting
confidence: 82%
“…The role of parental involvement that has a positive and significant effect on student performance is in line with some previous relevant research [21,22]. Purnomo and colleagues [2] stated that learning from home forces parents to be involved in their children's learning, especially their supervision of their children's work.…”
Section: Discussionsupporting
confidence: 82%
“…Students' attitudes and behaviors are directly affected by parent-child and parent-school involvement practices, which indirectly affects the student's achievement to various extent (McNeal, 2014). Parents' involvement positively influences the educational achievement of children (Wilder, 2014), especially mathematics performance (Huang et al, 2021;Otani, 2020;Pan et al, 2006). In the findings of other research, Gordon and Cui (2012) and Houtenville and Conway (2008) agreed that parental involvement in students' educations would lead to their children's better academic performance.…”
Section: Theoretical and Hypothesis Research Parental Influence On St...mentioning
confidence: 92%
“…As a result, the student's parents had a positive effect on their child's math performance if they paid attention to their child's learning and took concrete steps to improve their child's progress. It was observed that the close relationship between the student's parents and the child increases the student's self-confidence (Huang, 2021). The study was conducted in 21 countries to find a link between parent-child communication and academic achievement.…”
Section: Literature Reviewmentioning
confidence: 99%